(untitled) (E Global Congress, 2025)
In this report, the author expresses his views on the role of the European Union, which is one of the important directions in the foreign policy of the Central Asian republics in the modern era. The researcher has been engaged in this field for many years and tries to separately assess the role of a number of factors connecting Central Asia and the European Union - trade and energy, global security and challenges, the Afghan problem, transport and logistics, etc. According to the author, despite the fact that strategic relations between the parties have been defined as long-term cooperation since the 1990s, certain global geopolitical changes have affected this. In recent years, relations between the regions have been intensifying due to the participation of China and Russia in the region. The convergence of the positions of Uzbekistan and other Central Asian countries on the Afghan issue, as well as the positive environment in the region, are also contributing significantly to the quality of foreign relations.